ANALISIS PERSEPSI PELAKU UMKM DAN SOSIALISASI SAK EMKM TERHADAP DIBERLAKUKANNYA LAPORAN KEUANGAN YANG BERBASIS SAK EMKM: Persepsi pelaku UMKM, Sosialisasi SAK EMKM dan Penggunaan SAK EMKM Persepsi pelaku UMKM, Sosialisasi SAK EMKM dan Penggunaan SAK EMKM - Viola Syukrina E Janrosl (Jurnal Akuntansi Keuangan dan Bisnis, 2018)
This study aims to determine the perception of MSME actors towards the implementation of financial statements based on SAK EMKM January 1, 2018 and to socialize SAK EMKM to MSME players who do not know the SAK EMKM. Currently many MSME players face various problems, one of the problems is the difficulty of UMKM getting loan funds in the form of bank loans as additional business capital. This is due to the weakness of human resources (HR) in preparing financial statements. The ability of MSMEs in facing the progress of global competition is indeed very necessary because this can maintain the stability of MSMEs and the economy in Indonesia. The population of this research is 340 MSMEs in Sagulung Subdistrict registered in the Batam City PMP-KUKM Department totaling 340. The samples taken in this study the UMKM business operators in Sagulung Sub-District registered in Batam City PMP-KUKM Service were determined using the Slovin formula of 100. The research data will be processed using SPSS version SAK EMKM 22. The results of this study Perceptions of micro, small and medium enterprises do not significantly influence the use of SAK EMKM. SAK EMKM socialization has a significant effect on the use of SAK EMKM. Perceptions of micro and small and medium enterprises and the socialization of SAK EMKM have a significant effect on the use of SAK EMKM. The magnitude of the effect of the independent variable on the dependent variable is 53.9% which is indicated by R Square which means the use of SAK EMKM. Influenced by the perception of micro and small and medium businesses and the socialization of SAK EMKM by 53.9% while 46.1% is influenced by other variables which was not included in this study